ANALISIS FRAMING BERITA KEKERASAN SEKSUAL PADA MEDIA MASSA ONLINE SERAMBINEWS.COMPERIODE 2020-2021 - Ridwan Muhammad Hasan Ridwan Muhammad Hasan; Cut Salma (Jurnal Komunikasi dan Media, 2025)
The prevalence of sexual violence in today’s society is frequently highlighted in mass media, further amplified by the advancement of technology. While such news should ideally serve as beneficial information to foster empathy and caution, the current landscape of sexual violence reporting is deeply concerning. Mass media often exposes explicit details of sexual activities, leading to reports that contain obscene elements. Journalistic practices should strictly adhere to the Journalistic Code of Ethics (KEJ); specifically, Article 4 as regulated by the Indonesian Journalists Association (PWI) prohibits the publication of false, sadistic, and obscene content. This article interprets that news should not provide vulgar descriptions of sexual acts through imagery or text that could incite lust. Motivated by these issues, this study examines how mass media, particularly online media with its heterogeneous nature, should frame reports on sexual violence. The research addresses two primary problems: the framing of sources' statements in sexual violence news on Serambinews.com and the media’s partiality in reporting issues involving both male and female victims. Utilizing a qualitative approach with Robert N. Entman’s critical framing analysis encompassing Define Problem, Diagnose Causes, Make Moral Judgment, and Treatme Recommendation the findings indicate that the studied media still violates Article 4 of the PWI Journalistic Code of Ethics. This is evidenced by news texts that frame sexual violence with obscene elements and provide vulgar descriptions of sexual activities.